Bacterioplankton response to nitrogen and dissolved organic matter produced from salmon mucus - Molina, Verónica; Fernández, Camila (MicrobiologyOpen (Weinheim), 2020)
Aquaculture releases organic matter to the water column through excretion, fecal pellets, and uneaten food, but also by the continuous release of fish epithelium mucus. The effect of the latter on natural bacterial assemblages was determined using ammonium amended experiments at Puyuhuapi fjord in Chilean Patagonia. Mucus was added to seawater coming from 2 and 100 m depth and ammonium, nitrite and nitrate, dissolved organic carbon (DOC), picoplankton abundance, and active composition (i‐tag 16S rRNA) were followed for 24 h. The results showed a significant response from the microbial community but only at surface depth after 2 and 6 h of incubation. A reduction of DOC and ammonium concentration and accumulation of nitrite and nitrate over time was observed, mainly at 100 m. Changes in the composition of active bacteria between treatments were observed at different taxonomic levels, associated with Alphaproteobacteria (Clade SAR11), Bacteroidetes (Polaribacter) and Gammaproteobacteria (Colwellia, Oceaniserpentilla) and other bacteria such as Nitrospina sp, a nitrite‐oxidizing bacteria at some hours during the incubation. Fish pathogens, such as Vibrio and Piscirickettsia were rare (<0.02%). Overall, our study suggests that fish mucus can cause rapid modifications in microbial assemblages and stimulate organic matter and nutrient cycling, including heterotrophic and autotrophic (nitrification) in areas influenced by aquaculture. Salmon farming can modify ambient microbial community structure, including specific groups like marine nitrifying bacteria. Fish mucus represents an additional source of dissolved organic matter and nutrients to the water column. There is a rapid response of fjord free‐living microbial community to mucus addition.